ANALISIS PERBANDINGAN UJI KEAUSAN ANTARA KAMPAS KOPLING KUALITAS 1 DENGAN KUALITAS 2 PADA KENDARAAN SUZUKI KATANA - Aryananta Lufti; Harjanto, Budi; Silitonga, Frangky (JURNAL MEKANIKASISTA, 2025)
To support high mobility and varied terrain, vehicles must have optimal engine performance, especially in the clutch system, which is prone to slipping due to clutch lining wear, increasing the risk of accidents. This study analyzes the wear level of Suzuki Katana clutch linings by comparing KW 1 and KW 2 through hardness, wear, and carbon content tests. The results indicate that KW 1 has a hardness of 251.34 kg/mm², higher than KW 2, which is only 67.82 kg/mm². The wear value of KW 1 is 0.003×10⁻⁴ mm³/kg.m, lower than KW 2 at 0.0086×10⁻³ mm³/kg.m. The carbon content in KW 1 reaches 44.0739%, higher than KW 2 at 32.3462%. These findings show that the higher the hardness of the clutch lining, the lower its wear rate, making KW 1 a better choice as it is more durable and resistant to wear.